2012
DOI: 10.1515/jpm-2012-0145
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth Genome Project (PGP) – validation of resources for preterm birth genome-wide studies

Abstract: We determined a series of quality control (QC) analyses to assess the usability of DNA collected and processed from different countries utilizing different DNA extraction techniques prior to genome-wide association studies (GWAS). The quality of DNA collected utilizing four different DNA extraction techniques and the impact of shipping DNA at different temperatures on array performance were evaluated. Fifteen maternal-fetal pairs were used from four countries. DNA was extracted using four approaches: whole blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
(7 reference statements)
0
2
1
Order By: Relevance
“…The reasons for preterm delivery are very heterogeneous and still unclear. A few studies suggested some gene polymorphisms were associated with preterm birth, but these findings were not confirmed in the other studies (6,19). According to our results, no association was observed between CNR2 rs35761398 and the risk of extremely premature birth.…”
Section: Discussioncontrasting
confidence: 99%
“…The reasons for preterm delivery are very heterogeneous and still unclear. A few studies suggested some gene polymorphisms were associated with preterm birth, but these findings were not confirmed in the other studies (6,19). According to our results, no association was observed between CNR2 rs35761398 and the risk of extremely premature birth.…”
Section: Discussioncontrasting
confidence: 99%
“…Suitable numbers of individuals with more restricted phenotypes, including gestational age windows at birth, type of spontaneous delivery (spontaneous labor versus premature rupture of membranes), associated fetal growth characteristics or maternal characteristics, will greatly accelerate gene identification. To facilitate time-efficient collection of subject samples (mother, father and infant at a minimum; maternal grandparents and more extended family structure when likely to be informative) and phenotype data, more extended international collaborations with comprehensive, standardized definitions and data fields are essential [69]. Ultimately, gene discovery in humans will require the innovative application of noninvasive methods during pregnancy, such as functional imaging, proteomics and metabolomics, as well as the generation and investigation of new preclinical model organisms and ex vivo systems, to establish mechanisms and define potential prophylactic interventions for preterm birth.…”
Section: Conclusion and Future Approachesmentioning
confidence: 99%
“…Identification of genetic variants that associate with SPTB is ongoing, and an international preterm labor genetic consortium that includes participants from multiple ethnic/racial groups has been formed. 11 Owing to the large number and complexity of the factors that affect SPTB, such a multidisciplinary, multiregional approach will be required.…”
mentioning
confidence: 99%